Electro-optic and intensity-based terahertz peak field evaluation: comparison, challenges and perspectives - X Ropagnol; C M Garcia-Rosas; H Uchida; F Blanchard; T Ozaki (JPhys Photonics)
The complete characterization of intense terahertz (THz) sources is vital for predicting, simulating and analyzing the nonlinear interaction between matter and intense THz fields. Although there is little debate about the experimental method used to measure the time-domain profile and spectra, after more than thirty years since the first generation of an intense THz pulse by optical means, the THz community has still not elaborated a standardized protocol for measuring the peak intensity and the peak electric field of these pulses. Indeed, different protocols, tools and experimental conditions are used to measure the peak field. Here, we compare two commonly used methods for measuring the peak field of intense THz pulses generated from organic crystals and pumped by energetic, femtosecond, near-infrared optical pulses. The first method evaluates the peak field directly from the phase variation in the polarization state of an optical probe laser pulse induced by the THz field via the electro-optic effect. In contrast, the second method indirectly calculates the peak field from three experimental parameters: the duration, energy, and spot size of the THz pulse, which determine the peak intensity. Our investigation indicate that the direct method likely underestimates the peak field due to its inherent limitations, while the indirect method significantly overestimates it. Despite conservatively measuring the parameters required for the indirect method, we found that it yields a peak field nearly three to ten times larger than the direct method. Additionally, we highlight that the higher the frequency components of the pulse, the larger this ratio becomes. We attribute this discrepancy mainly to the sensitivity of the measurement equipment, namely thermal imaging cameras and pyroelectric detectors, whose sensitivity increases significantly at higher frequency, posing a challenge when measuring the energy and spot size of the THz pulse. In light of this, we encourage the THz community to establish a standardized measurement protocol for peak field evaluation.